The Role and Strategy of Educators in Improving the Quality of Students' Ability to Read the Quran Students - Wulandari, Putri; Safarudin, Rizal; Zulfamanna, Zulfamanna (STIT Ahlussunnah Bukittinggi, 2025)
The ability to read the Quran is one of the basic competencies that is the main focus of non-formal Islamic religious education. Quranic Education Institutions serve as learning spaces that support the mastery of this skill through various learning approaches and strategies tailored to the characteristics of the students. This study aims to analyze the role and strategies of educators at Quran Education Institutions in improving the quality of students' Quran reading skills, as well as to identify the supporting and inhibiting factors that influence this process. This study uses a qualitative method with a case study approach. Data sources were obtained from educators at the Quran Education Institution, parents, and students involved in learning activities at the Quran Education Institution. Data collection was carried out through observation, interviews, and documentation. The data were analyzed through the stages of data reduction, data presentation, and gradual conclusion drawing. The results of the study indicate that educators play a role in improving Quran reading skills through the application of the Iqra' method with classical learning techniques, such as educators reading and students listening, educators reading and students imitating, as well as reading together and reading comprehension activities. These strategies contribute to supporting the process of learning to read the Quran, although the achievement of students' abilities is influenced by their level of involvement and learning conditions. The implications of this study indicate that strengthening the role of educators in applying structured and contextual learning strategies can support the improvement of the quality of Quran reading learning in Quranic Education Institutions.